2020
DOI: 10.1021/acsnano.0c05851
|View full text |Cite
|
Sign up to set email alerts
|

Atomic and Electronic Structure of a Multidomain GeTe Crystal

Abstract: Renewed interestRashba semiconductors in non-volatile spintronic devices with advanced memory and computing capabilities at the nanoscale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 68 publications
2
21
0
Order By: Relevance
“…We obtained the surface Rashba band for a wide range of k z dimensions through experimental ARPES measurements with linearly polarized light. The dispersion of the Rashba band was well matched with previous reports, which used the epitaxially grown GeTe films [20,22] and single-crystalline sample [33]. We used in situ potassium dosing (K dosing) to systematically control the binding energy and splitting energy of the surface Rashba state and observed a decrease in the Rashba splitting after K dosing.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…We obtained the surface Rashba band for a wide range of k z dimensions through experimental ARPES measurements with linearly polarized light. The dispersion of the Rashba band was well matched with previous reports, which used the epitaxially grown GeTe films [20,22] and single-crystalline sample [33]. We used in situ potassium dosing (K dosing) to systematically control the binding energy and splitting energy of the surface Rashba state and observed a decrease in the Rashba splitting after K dosing.…”
Section: Introductionsupporting
confidence: 81%
“…The bands located at k y = 0.31 and 0.2 Å −1 correspond to the outer and inner branch of the SS1, respectively. Because of its 2D nature, SS1 and SR show negligible dispersion along the k z [23,33].…”
Section: Discussionmentioning
confidence: 99%
“…During ex-situ transfer to ultrahigh vacuum (UHV) the sample was mounted on an STM puck. We performed a detailed STM investigation to study the atomic structure of the polycrystalline PtTe 2 film, similar to previous studies focused on other materials 29,42 . The 1 T atomic structure of PtTe 2 is schematically represented in Fig.…”
Section: Stm Characterization Of Point Defectsmentioning
confidence: 99%
“…Moreover, recent reports have indicated that damage by the TEM electron beam can be a problematic issue for TMDs. [37][38][39] On the other hand, scanning tunnelling microscopy and spectroscopy (STM/STS) are non-destructive techniques, which can be used to map morphology and probe the electronic structure of samples [40][41][42][43] and, provided a conductive pathway can be established through the sample, do not require a transfer process.…”
Section: Introductionmentioning
confidence: 99%